2019
DOI: 10.33321/cdi.2019.43.39
|View full text |Cite
|
Sign up to set email alerts
|

Influenza epidemiology in patients admitted to sentinel Australian hospitals in 2017: the Influenza Complications Alert Network (FluCAN)

Abstract: The Influenza Complications Alert Network (FluCAN) is a sentinel-hospital-based surveillance program that operates at sites in all jurisdictions in Australia. This report summarises the epidemiology of hospitalisations with laboratory-confirmed influenza during the 2017 influenza season. In this observational surveillance system, cases were defined as patients admitted to any of the 17 sentinel hospitals with influenza confirmed by nucleic acid detection. Data are also collected on a frequency-matched control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…Most people experience mild to moderate influenza illness only once or twice in their lifetime, with symptoms ranging from fever, cough, sore throat, body aches, and fatigue. However, the risk of severe influenza illness, which often requires hospitalization and can result in death, is more pronounced in the elderly, with increased occurrence, higher hospitalization rates, and increased morbidity and mortality compared with younger adults . This is exemplified by the data obtained from 17 Australian major hospitals during the 2015 April–October influenza season, with the elderly (≥65 yr) accounting for 46% of all hospitalized influenza‐infected patients out of 2070 laboratory‐confirmed cases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people experience mild to moderate influenza illness only once or twice in their lifetime, with symptoms ranging from fever, cough, sore throat, body aches, and fatigue. However, the risk of severe influenza illness, which often requires hospitalization and can result in death, is more pronounced in the elderly, with increased occurrence, higher hospitalization rates, and increased morbidity and mortality compared with younger adults . This is exemplified by the data obtained from 17 Australian major hospitals during the 2015 April–October influenza season, with the elderly (≥65 yr) accounting for 46% of all hospitalized influenza‐infected patients out of 2070 laboratory‐confirmed cases .…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk of severe influenza illness, which often requires hospitalization and can result in death, is more pronounced in the elderly, with increased occurrence, higher hospitalization rates, and increased morbidity and mortality compared with younger adults . This is exemplified by the data obtained from 17 Australian major hospitals during the 2015 April–October influenza season, with the elderly (≥65 yr) accounting for 46% of all hospitalized influenza‐infected patients out of 2070 laboratory‐confirmed cases . Elderly individuals, particularly men, also preferentially succumbed to severe avian H7N9 influenza disease .…”
Section: Introductionmentioning
confidence: 99%
“…In recent influenza seasons in Australia, 91% of influenza‐related deaths were in people aged ≥65 years, and almost all influenza‐related deaths occurred in patients with chronic medical conditions . A 2018 Cochrane review identified that IIV reduces the risk of influenza in the elderly with number needed to treat being 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The Australian National Immunisation Program (ANIP) recommends annual inactivated influenza vaccination (IIV) of the elderly (≥65 years), and younger patients with chronic conditions—those at high risk of severe influenza . However, under 80% of elderly Australians, and 60% of eligible younger adults received influenza vaccine annually . Recent data suggest that the ANIP prevents approximately 46% of influenza‐related hospital admissions, and increasing coverage in at‐risk groups could further reduce this by 14% .…”
Section: Baseline Demographic and Clinical Characteristics And Breakdmentioning
confidence: 99%
See 1 more Smart Citation